Pengukuran Validitas Website â€œmengundangkamu.onlineâ€ Menggunakan SPSS dengan Kombinasi Metode R-Table dan Coehnâ€™s Cappa - Parlika, Rizky; Shahab, Muhammad Syaugi; Nurilhaq, Muhammad Sabilli; Firmansyah, Fahrul; Prayoga, Julio Cahya (JURNAL TEKNIK INFORMATIKA UNIS, 2022)
In this study, the validity test was carried out on the website "inviting you.online" by calculating the validity value of the respondents' answers to the questionnaire to determine the level of operational feasibility of the website. Meanwhile, the questions from the questionnaire are the attributes contained on the website with a sample of 30 students and college students in the East Java region randomly and when the research was conducted in July 2022. From the results of processing the questionnaire data using SPSS by applying the method R-Table and the combination of Coehn's Cappa, then the R-Table method obtained the percentage of validity of 100% and invalidity of 0%. Then, with the combination of the Coehn's Cappa method, a value of 0.737 was obtained with a significant value of 0.016, which is where the level of strength of the appraiser's agreement on the website is moderate.